2013
DOI: 10.1007/s00277-013-1937-4
|View full text |Cite
|
Sign up to set email alerts
|

Younger patients with chronic myeloid leukemia do well in spite of poor prognostic indicators: results from the randomized CML study IV

Abstract: Since the advent of tyrosine kinase inhibitors, the impact of age on outcome of chronic myeloid leukemia (CML) patients has changed. We therefore analyzed patients from the randomized CML study IV to investigate disease manifestations and outcome in different age groups. One thousand five hundred twenty-four patients with BCR-ABL-positive chronic phase CML were divided into four age groups: (1) 16–29 years, n = 120; (2) 30–44 years, n = 383; (3) 45–59 years, n = 495; and (4) ≥60 years, n = 526. Group 1 (adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 45 publications
7
47
0
Order By: Relevance
“…The authors subdivided the CML patients by age, describing 120 patients aged 16-29 years that made up the AYA group for this analysis. Similar to Pemmaraju et al [5], Kalmanti et al [16] found that CML AYA patients made up 8% of the overall CML population studied and exhibited more splenomegaly and also a higher white blood cell count as compared to older CML patients, thus suggesting that AYAs may have more aggressive features. An additional finding of this study demonstrated that AYA CML patients had a higher rate of BCR-ABL transcript levels greater than 10% on the international scale at the 3-month time point as compared to older patients, a feature recognized as an early indicator of poor long-term outcome.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The authors subdivided the CML patients by age, describing 120 patients aged 16-29 years that made up the AYA group for this analysis. Similar to Pemmaraju et al [5], Kalmanti et al [16] found that CML AYA patients made up 8% of the overall CML population studied and exhibited more splenomegaly and also a higher white blood cell count as compared to older CML patients, thus suggesting that AYAs may have more aggressive features. An additional finding of this study demonstrated that AYA CML patients had a higher rate of BCR-ABL transcript levels greater than 10% on the international scale at the 3-month time point as compared to older patients, a feature recognized as an early indicator of poor long-term outcome.…”
Section: Discussionsupporting
confidence: 53%
“…More recently, Kalmanti et al [16] performed an analysis on the German CML study IV data set, which includes 1,520 CML patients of all ages enrolled in a randomized trial. The authors subdivided the CML patients by age, describing 120 patients aged 16-29 years that made up the AYA group for this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…There have been two large retrospective studies focusing on CML in AYA patients treated with TKIs [22,23]. Pemmaraju et al evaluated 468 CML-CP patients treated with TKIs as initial therapy at one institution in U.S. AYA patients, aged 15-29 years, accounted for 61 (13 %) of the total patients in this study cohort [22].…”
Section: Discussionmentioning
confidence: 98%
“…In that study, the rate of achieving CCyR, major molecular response (MMR), and complete molecular response (CMR) were significantly lower in AYA than older patients [22]. Another retrospective study demonstrated that AYA patients had more clinically aggressive features than older patients without significant differences in the response to the treatment [23]. However, no such data are available for a Japanese population at present.…”
Section: Introductionmentioning
confidence: 88%
“…Rick Proschmann, 1 Christoph Baldow, 1 Tino Rothe, 1 Meinolf Suttorp, 2 Christian Thiede, 3 Josephine T. Tauer, 2 Martin C. Müller, 4 Andreas Hochhaus, 5 Ingo Roeder 1,6 and Ingmar Glauche …”
mentioning
confidence: 99%